Virtual bronchoscopic navigation for peripheral pulmonary lesions - Asano, Fumihiro; Eberhardt, Ralf; Herth, Felix (Respiration, 2014)
Virtual bronchoscopic navigation (VBN) is a method in which the bronchoscope is guided on the bronchial route to a peripheral lesion using virtual bronchoscopic images. In reports on VBN for peripheral pulmonary lesions searched in PubMed as of November 2013, the diagnostic yield by ultrathin bronchoscopy in combination with computed tomography and VBN was within the range of 65.4-81.6%. Using endobronchial ultrasonography with a guide sheath (EBUS-GS) and VBN, it was between 63.3 and 84.4%, and using X-ray fluoroscopy and VBN, it was between 62.5 and 78.7%. The overall diagnostic yield was 73.8% [95% confidence interval (CI) 70.9-76.8%] and that for lesions ≤2 cm was 67.4% (95% CI 63.3-71.5%). These values indicate high diagnostic rates. In randomized comparative trials, the combination of VBN with EBUS-GS improved the diagnostic yield and shortened the examination time. The diagnostic yields for lesions in the right upper lobe, those invisible on posterior-anterior radiographs and those located in the peripheral third of the lung field were improved by VBN on ultrathin bronchoscopy in combination with X-ray fluoroscopy. The usefulness of VBN was also found on meta-analysis. Taken together, VBN is a promising navigational bronchoscopy method as it requires no specific training, has a low overall complication rate of 1.0% (95% CI 0.2-1.8%) and does not directly induce or cause severe complications. To maximize the full potential of VBN and promote its use, investigation of cases in which it is useful, determination of the optimum combination of procedures, a cost/benefit analysis and advancement of the VBN system are warranted.
Gesehen am 15.10.2020